Bahan Ajar Menyimak untuk Pelajar BIPA Tingkat Pemula Tinggi - Yeni Dwi Rahayu Ningtyas; Kusubakti Andajani; Gatut Susanto (Graduate School of Universitas Negeri Malang, 2021)
Abstract: The aim of the development of the teaching material is to produce a prototype of teaching material that focuses on improving the listening skill in learning Indonesian for Foreigners (BIPA). The teaching material developed using American Council on the Teaching of Foreign Language (ACTFL) as the reference of material development based on the level of language skill of the students. The listening teaching material obtained a score of 60% on the aspect of the content of teaching material, 58% on the aspect of the systematic of teaching material, 62% on the aspect of the language uses of teaching material, and 60, 41% on the aspect of the layout of teaching material. Based on the score obtained, the teaching material developed is in the category of “feasible enough to be implemented” and need to revise based on the criticisms, suggestions, and comments from the learning experts and practitioners of BIPA.Abstrak: Pengembangan bahan ajar ini bertujuan untuk menghasilkan prototype bahan ajar yang berfokus pada peningkatan kemampuan menyimak pada pembelajaran bahasa Indonesia bagi Penutur Asing (BIPA). Bahan ajar ini dikembangkan menggunakan American Council on the Teaching of Foreign Language (ACTFL) sebagai acuan pengembangan materi berdasarkan tingkat kemampuan berbahasa pelajar. Bahan ajar menyimak ini memperoleh skor 60% pada aspek isi bahan ajar, 58% pada aspek sistematika bahan ajar, 62% pada aspek penggunaan bahasa bahan ajar, dan 60,41% pada aspek tampilan bahan ajar. Berdasarkan pemerolehan skor tersebut, bahan ajar yang dikembangkan ini masuk dalam kategori “cukup layak diimplementasikan” dan diperlukan revisi-revisi berdasarkan kritik, saran, dan komentar dari ahli pembelajaran BIPA dan praktisi-praktisi BIPA.